Diagnostic Efficacy of Four Methods for Locating the Second Canal of the Mesiobuccal Root of Maxillary Molars - Bello, Mariana De Carlo; Tibúrcio-Machado, Camilla; Londero, Clacir Dotto; Barletta, Fernando Branco; Moreira, Carlos Heitor Cunha (Iranian Endodontic Journal, 2018)
Introduction: The major cause for failure of root canal therapy is the inability to recognize the presence of all canals of the root canal system. Auxiliary tools, such as magnifying loupe, operative microscope and computed tomography (CT) images are used to facilitate the location of canals. The objective of the present survey was to evaluate the diagnostic efficacy of four methods for detecting the second canal of mesiobuccal roots (MB2) of permanent maxillary molars. Methods and Material: A total of 147 extracted human maxillary molars were assessed. The floor of the pulp chamber was inspected by an endodontist to find MB2 canals. Analyses were performed without magnification (direct visual method), using a loupe (with 3.5× magnification), and using a microscope (with 16× magnification). A fourth analysis was conducted using cone-beam computed tomography (CBCT) images. Teeth were sectioned horizontally into three parts (cervical, medial and apical thirds) to confirm the presence of MB2 canals (reference standard method). Sensitivity, specificity, and positive/negative predictive values were calculated for each method. Results: No statistically significant differences were observed in the frequency of MB2 found between the microscope and the reference standard or between CBCT and the reference standard. CBCT had higher sensitivity (0.88), specificity (0.88), positive (0.84) and negative (0.91) predictive value than the other three methods. Conclusion: CBCT was the most accurate method for detecting the MB2 and it had a diagnostic efficacy similar to that of the reference standard method. Keywords: Cone-beam Computed Tomography; Diagnosis; Data Accuracy; Endodontic; Root Canal Therapy